PARADIGMATIC FRAMEWORK OF DEMOCRATIC AND HUMANIST ISLAMIC EDUCATION - Sri Haryanto (Institute of Computer Science (IOCS), 2022)
This research is qualitative research that aims to find and find how the paradigmatic framework of Islamic education is democratic and humanistic, research information is sourced from literature. Amid globalization, Islamic education is not only required to be able to print the younger generation of the nation who have reliable intellectual intelligence but Islamic education is also expected to print generations who are emotionally intelligent, spiritual and graceful in morals. Therefore, Islamic education should not only be oriented toward the